Country image in the context of European Union membership: The Turkish case - (:unkn) unknown (My University, 2008)
Purpose - The purpose of this paper is to investigate the opinions of owners/managers of Turkish furniture firms on country image effects of expected improvements in Turkey's democratic, economic, and political life resulting from Turkey's likely EU membership. Design/methodology/approach - Survey-based empirical data are analyzed via multiple regression analysis. Findings - The paper finds that political and economic influences of EU negotiations will improve country image, whereas democratic influences will not have a significant effect. Research limitations/implications - The study is conducted in one industry and findings may not be generalizable. As opinions on country image are affected by discussions in the media or temporary situations between EU countries and Turkey, the study should be repeated at regular intervals. Official bodies need to make sure that reforms made in the democratic arena are well communicated to business communities. Also, business communities can promote implementation of democratic adjustment efforts by joining democratic establishments. Originality/value - Most previous studies on country of origin (COO) effects were conducted with high risk or very low risk product groups. In this paper, a mid-level risk product category, furniture, is examined with respect to country image.
Keywords: Country of origin; European Union; Furniture industry; Manufacturing industries; Product image; Turkey